(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
The emerging field of the Science of Cities has revealed universal power-law trends in urban scaling, transcending cultural and geographic variations. This study investigates the interplay between fundamental allometry, fractal dimensions, and city social dynamics. By linking these factors to the hierarchical social structures defined by Dunbar’s numbers, a causal relationship is established that illuminates the drivers of urban scaling. Notably, this research highlights the pivotal role of the Big Five personality traits in shaping the fractal nature of urban environments. These findings bridge the gap between human cognitive traits and urban structural patterns, offering a novel perspective on the universality of urban scaling and opening new opportunities for interdisciplinary exploration.